2015
DOI: 10.1038/nature15748
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-mesenchymal transition is not required for lung metastasis but contributes to chemoresistance

Abstract: The role of epithelial to mesenchymal transition (EMT) in metastasis is a longstanding source of controversy, largely due to an inability to monitor transient and reversible EMT phenotypes in vivo. We established an EMT lineage tracing system to monitor this process, using a mesenchymal-specific Cre-mediated fluorescent marker switch system in spontaneous breast-to-lung metastasis models. We confirmed that within a predominantly epithelial primary tumor, a small portion of tumor cells undergo EMT. Strikingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

83
1,439
4
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,567 publications
(1,535 citation statements)
references
References 35 publications
83
1,439
4
9
Order By: Relevance
“…For example, elevated expression of IL6 and other chemoresistance‐related genes accompanies the EMT in a mouse breast cancer model (Fischer et al ., 2015). Our finding that ZEB1 and ZEB2 are inducers of inflammatory cytokines is supported by a report by Suarez‐Carmona et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, elevated expression of IL6 and other chemoresistance‐related genes accompanies the EMT in a mouse breast cancer model (Fischer et al ., 2015). Our finding that ZEB1 and ZEB2 are inducers of inflammatory cytokines is supported by a report by Suarez‐Carmona et al .…”
Section: Discussionmentioning
confidence: 99%
“…ZEB2 expression is also reported to be associated with poor prognosis of several types of cancer, although less frequently than ZEB1 (Fang et al ., 2013; Prislei et al ., 2015). It was recently reported that the EMT is involved in cancer malignancy by contributing not only to metastasis but also to the acquisition of cancer stem cell properties and chemoresistance (Fischer et al ., 2015; Ye and Weinberg, 2015; Ye et al ., 2015; Zheng et al ., 2015). A recent genome‐wide analysis of EMT‐related transcription factor binding regions in pancreatic cancer cells suggested that ZEB1 plays a role in inducing the mesenchymal phenotype by suppressing enhancers that regulate the expression of epithelial genes (Diaferia et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this con text, not all can cer cells un dergo EMT to suc cess fully metas ta size. Un like many in vitro stud ies, in vivo mod els of breast car ci noma and pan cre atic duc tal ade no car ci noma (PDAC) sug gest that EMT is dis pens able for ef fi cient metas ta sis de vel op ment [232,233]. Nev er the less, EMT af fected in both model chemosen si tiv ity in a tis sue de pen dent man ner.…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…Nev er the less, EMT af fected in both model chemosen si tiv ity in a tis sue de pen dent man ner. In deed, in breast can cer the mes enchy mal like can cer cells pro lif er ated less, which made them more re sis tant to con ven tional chemother apy [232], while in PDAC mes enchy mal like can cer cells up reg u lated nu cle o sides trans porters, which made them more sen si tive to gem c itabine. In ter est ingly, if EMT pro motes the ini tial steps of the metasta tic process, the re versed process, the mes enchy mal to ep ithe lial tran si tion (MET) seems im por tant in the later steps of metas ta sis de vel op ment [234].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…It also promotes the generation of cancer stem cells, thereby contributing to tumor recurrence and metastasis (10,11). Two recent publications have challenged this dogma for breast and pancreatic cancers and have suggested instead that EMT confers chemoresistance rather than metastatic potential to tumor cells (12,13). In the case of HCC, growing evidence suggests that EMT contributes to metastasis and poorer patient prognosis (14)(15)(16)(17).…”
mentioning
confidence: 99%